Application of inductive learning: Air pollution forecast in Istanbul, Turkey - Karaca, F; Alagha, O; Ertürk, F (TECH SCIENCE PRESS, 2005)
In this study, Istanbul city was taken as the study area. A new and powerful technique, Artificial Intelligence (AI), an Inductive Learning Algorithm (RULES-3), was used in predicting the future (next 24 hours) sulfur dioxide (SO2) air pollutant on the basis of various meteorological parameters. The goal of this study is to forecast the 24-h average SO2 concentration levels in the urban atmosphere using AI. As a result of this study, it was seen that Al is a powerful tool in estimating air pollution levels considering the complex and nonlinear structure of the atmospheric parameters, which is the source of the database.
Keywords: air pollution forecasting; inductive learning; RULES-3; SO2; ENVIRONMENTAL DATA; TIME-SERIES; OZONE; MODEL; Automation & Control Systems; Computer Science